2013
DOI: 10.1002/jmor.20205
|View full text |Cite
|
Sign up to set email alerts
|

Notable plesiomorphies and notable specializations: Head structure of the primitive “tongue moth” Acanthopteroctetes unifascia (lepidoptera: Acanthopteroctetidae)

Abstract: The Acanthopteroctetidae are one of the first-originated family-group lineages within "tongue moths" (Lepidoptera-Glossata). The purpose of this study is to provide a comprehensive account (based on whole mount preparations, serial sections, and Scanning electron microscopy) of the cephalic structure of an adult exemplar of the family, to supplement the sparse available information. Notable plesiomorphies include the retention of frontal retractors of the narrow labrum, a high supraocular index linked to stron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…The transformation of the generalized galeae into the coilable proboscis/tongue initially took place with surprisingly little modification of the maxillary musculature (Kristensen, ; Krenn & Kristensen, ). In contrast, the physical properties of the proboscis wall (with cuticle elasticity enabling nonmuscle‐aided recoil), as well as details of its specialized surface configuration such as the linking mechanism (Krenn & Kristensen, ; Kristensen et al , ), have in eriocraniids, acanthopteroctetids and lophocoronids a remarkable similarity, which surely reflects the acquisition of these specializations in the stem lineage of Glossata (node 8). Loss of mandibular function in the postpharate adult stage, and associated reduction of mandibular sclerotization and loss of mandibular teeth and cranial articulation are additional glossatan ground plan autapomorphies associated with the reorganization of the feeding apparatus, and so is the loss of a prominent epistomal sulcus; in the maxillary palp, the flexor muscle between segments 2 and 3 is lost.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The transformation of the generalized galeae into the coilable proboscis/tongue initially took place with surprisingly little modification of the maxillary musculature (Kristensen, ; Krenn & Kristensen, ). In contrast, the physical properties of the proboscis wall (with cuticle elasticity enabling nonmuscle‐aided recoil), as well as details of its specialized surface configuration such as the linking mechanism (Krenn & Kristensen, ; Kristensen et al , ), have in eriocraniids, acanthopteroctetids and lophocoronids a remarkable similarity, which surely reflects the acquisition of these specializations in the stem lineage of Glossata (node 8). Loss of mandibular function in the postpharate adult stage, and associated reduction of mandibular sclerotization and loss of mandibular teeth and cranial articulation are additional glossatan ground plan autapomorphies associated with the reorganization of the feeding apparatus, and so is the loss of a prominent epistomal sulcus; in the maxillary palp, the flexor muscle between segments 2 and 3 is lost.…”
Section: Discussionmentioning
confidence: 99%
“…A few morphological specializations shared between Acanthopteroctetidae and Neopseustidae have, in fact, been found, mainly in the antenna: the smooth intercalary sclerotization and the alignment of antennal scale sockets in longitudinal rows. Also, the prominent peg‐and‐socket type of neopseustid scapo‐pedicellar articulation is to some degree approached in Acanthopteroctetes (Kristensen et al , ). The narrowed labrum, which is present in Acanthopteroctetes and Neopseustis Meyrick, can with some certainty be considered a parallelism, as the neopseustids Apoplania and Synempora Davis & Nielsen have the ancestral, broader and more pentagonal type, and, importantly, the overall generalized neopseustid Nematocentropus Hwang also has a broad labrum (Davis, ; Kristensen et al , ; N.P.…”
Section: Discussionmentioning
confidence: 99%
“…Recent discoveries in South America (Kristensen et al 2013) and South Africa (Mey 2011) demonstrated that the genus and family have a much larger distribution on the globe, which is in agreement with the antiquity of the group that is certainly of Mesozoic age (Grimaldiand Engel 2005).…”
Section: Introductionmentioning
confidence: 56%
“…Nye and Fletcher (1991: p.xiv) included the family in Acanthopteroctetidae (without providing a formal synonymization however) and this view was followed by most subsequent authors (Nielsen and Kristensen 1996;Kristensen 1998;Kristensen et al 2007;Kristensen et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…) as in Acanthopteroctetes sp. (Kristensen et al ., ) and the collembolan Tomocerus flavescens (Eisenbeis & Wichard, ).…”
Section: Compound Eye Research Suggestionsmentioning
confidence: 99%